ClusterJoin: A Similarity Joins Framework using Map-Reduce - Sarma, Akash Das; He, Yeye; Chaudhuri, Surajit (Proceedings of International Conference on Very Large Databases (VLDB), 2014)
Similarity join is the problem of finding pairs of records with similarity score greater than some threshold. In this paper we study the problem of scaling up similarity join for different metric distance functions using MapReduce. We propose a ClusterJoin framework that partitions the data space based on the underlying data distribution, and distributes each record to partitions in which they may produce join results based on the distance threshold. We design a set of strong [candidate filters] specific to different distance functions using a novel bisector-based framework, so that each record only needs to be distributed to a small number of partitions while still guaranteeing correctness. To address data skewness, which is common for high dimensional data, we further develop a [dynamic load balancing] scheme using sampling, which provides strong probabilistic guarantees on the size of partitions, and greatly improves scalability. Experimental evaluation using real data sets shows that our approach is considerably more scalable compared to state-of-the-art algorithms, especially for high dimensional data with low distance thresholds.